Analisis Mathematics Anxiety Ditinjau dari Tipe Kepribadian Sensing dan Intuiting - Arshinta Vrasetya; Eline Yanty Putri Nasution (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze students' mathematics anxiety based on Sensing and Intuiting personality types using the MBTI (Myers Briggs Type Indicator) test. Mathematics anxiety is a feeling of anxiety that interferes with students' ability to understand mathematical concepts. Students with the Sensing type focus more on concrete facts, while the Intuiting type relies more on patterns and abstract concepts. This study used a qualitative method with case studies of four 12th grade students at SMA Negeri 3 Sungai Penuh who were selected based on the results of the MBTI test. Data were obtained through a Likert scale-based mathematics anxiety questionnaire and observation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing to describe patterns of mathematics anxiety according to personality type. The results showed that Sensing-type students tended to experience higher math anxiety than Intuiting-type students. Sensing students had difficulty understanding abstract concepts, while Intuiting students were better able to see patterns and conceptual connections. These findings emphasize the importance of learning strategies tailored to personality types, such as a concrete approach for Sensing students and an exploratory method for Intuiting students, in order to reduce math anxiety and improve student understanding.